Pengembangan Model Pembelajaran Tematik Berbasis Aktivitas Siswauntuk Mengembangkan Kemampuan Menulis Narasi Siswa Kelas IVSekolah Dasar - Anwar, Rahmi; Morelent, Yetty; Alfino, Joni; Jendriadi, Jendriadi (Indonesian Research Journal on Education, 2023)
This study aims to explain the development process and product development of student activity-based thematic learning models to improve the narrative writing skills of fourth grade elementary school students that are valid, practical, and effective. The background of this research is that it begins with the low narrative writing skills of fourth grade elementary school students at SDN 19 Pasar Ambacang, Kuranji sub-district, Padang City. This type of research is development research. This study uses a 4-Dmodel consisting of 4 stages, namely the stage of defining, designing, developing, and disseminating. However, the dissemination stage was carried out in class IV SDN 19 Pasar Ambacang, Kuranji District, Padang City. The developed model was validated by experts. The practicality of the module is seen through the results of teacher and student responses as well as analysis of implementation and learning outcomes using the designed module. The results of this study indicate the following. First, the development process consists of three stages, namely the definition stage which analyzes the curriculum, concepts, and students. At the design stage, the module framework is designed and the module framework is written. Second, at the module development stage, validation results from experts were 84.70 with valid categories. There are two practical models based on practitioner responses, namely; first,the practicality by the teacher is 93.13 with a very practical category. Practicality by students in the first trial was 93.15 with a very practical category. The effectiveness of the developed model has an average of 86.7 with very effective qualifications. Based on the description of the data analysis, it can be concluded that the thematic learning model based on student activities is valid, practical and effective for improving the narrative writing skills of fourth grade elementary school students.